Solar-absorbing energy storage materials demonstrating superior solar-thermal conversion and solar-persistent luminescence conversion towards building thermal management and passive illumination - Yin, Yue; Chen, Hongbin; Zhao, Xi; Yu, Weitai; Su, Hua; Chen, Ying; Lin, Pengcheng (Energy conversion and management, 2022)
•Solar-absorbing energy storage materials are applied in building energy conservation.•Solar-absorbing energy storage materials possess a high solar absorbance of 91.93%.•Solar-absorbing energy storage materials present a high latent heat of 192.12 Jg−1. Nowadays, building energy consumption accounts for more than 50% of the total energy consumption. Exploiting advanced solar energy strategy is of great significance to achieve the building energy saving by spontaneously providing energy for a building. Herein, novel solar-absorbing energy storage materials constructed by solar-thermal conversion material, phase change material gel and persistent luminescence material are proposed to efficiently utilize the full spectrum of renewable solar energy towards the building thermal management and passive illumination. A flow chemical synthesis strategy is designed to continuously prepare the solar-thermal conversion material N, S-co-doped conjugated polybenzobisthiazole towards the robust solar energy harvesting (solar absorbance of 94.1%) and considerable thermal energy production (solar-thermal conversion efficiency of 88.3%). The liquid phase blending and sol–gel transition are proposed to fabricate the phase change material gels demonstrating high latent heat of 192.12 Jg−1 and self-supporting capacity, which can store the heat generated by N, S-co-doped conjugated polybenzobisthiazole and release the heat in the night. The persistent luminescence materials can absorb the ultraviolet–visible light in the solar spectrum in the daytime and emit the multicolour luminescence in the night. Taking advantages of the synergistic effect of the functional components, the proposed solar-absorbing energy storage materials demonstrate full spectrum utilization of solar energy (total solar absorbance of 91.93%) towards the building thermal management and passive illumination with a solar-light conversion efficiency of 1.65% and a solar-thermal conversion efficiency of 10.52%. The solar-absorbing energy storage materials create a state-of-the-art alternative for the next-generation energy saving buildings.